The Relationship Between Anthropometry and Jumping Performance in Handball: Anthropometry and Jumping Performance in Handball - Çıplak, Mustafa Ertuğrul; Eler, Nebahat; Eler, Serdar; Acar, Hakan (Progress in Nutrition, 2020)
Background: Anthropometric measurements are done for various purposes such as monitoring the growth and development of athletes, determining motor performance, physical activity and body composition changes and nutritional interventions. Aim: The aim of this study is to determine the relationship between anthropometry and jumping performances in 11-12-year-old girls handball players. Materials and Methods: 62 female handball players voluntarily participated in the study. Athlete’s height, body weight, body mass index (BMI), body fat ratio and measurements of whole arm, forearm, whole leg, thigh lengths, and elbow, waist, hip, calf, knee, ankle and wrist circumference were measured; reach length, single foot (right-left), double-feet vertical jumping and long jumping test by standing. The data were analyzed in SPSS 20 statistical program and Pearson correlation test was applied in statistical analysis, the significance value was determined as p <0.05. Results: There were correlations between athletes’ double-feet vertical jumping, all leg and thigh lengths and left-foot vertical jumping and thigh lengths positively; standing long-jumping and height, body weight and body fat ratio negatively; double-feet vertical jumping and body weight, body fat ratio negatively; left-foot vertical jumping and body fat ratio negatively (p<0.05). Conclusions: In conclusion, it was stated that leg length, body weight, body fat ratio may have an effect on jumping performance in 11-12-year-old female handball players.